1992
DOI: 10.1287/orsc.3.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Demography and Design: Predictors of New Product Team Performance

Abstract: The increasing reliance on teams in organizations raises the question of how these teams should be formed. Should they be formed completely of engineers or should they include a range of specialists? Should they be made up to people who have long tenure in the organization, or those with a wide range of experience? As teams increasingly get called upon to do more complex tasks and to cross functional boundaries within the organization, conventional wisdom has suggested that teams be composed of more diverse me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
1,078
5
17

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,452 publications
(1,157 citation statements)
references
References 51 publications
30
1,078
5
17
Order By: Relevance
“…It is widely recognized that customer feedback must be used to improve an innovative idea (Burpitt & Bigoness, 1997). To be effective, organizations need to manage their employees' relationships with internal and external members and other groups in order to bring information and other resources into the system (Gladstein, 1984;Ancona & Caldwell, 1992). Additionally, frequent contacts with the competitors have also been found to be vital.…”
Section: Social Capital and Iwbmentioning
confidence: 99%
“…It is widely recognized that customer feedback must be used to improve an innovative idea (Burpitt & Bigoness, 1997). To be effective, organizations need to manage their employees' relationships with internal and external members and other groups in order to bring information and other resources into the system (Gladstein, 1984;Ancona & Caldwell, 1992). Additionally, frequent contacts with the competitors have also been found to be vital.…”
Section: Social Capital and Iwbmentioning
confidence: 99%
“…On the other hand, this is balanced against evidence that there is a Group Processes & Intergroup Relations 9(4) 460 negative relationship between diversity, cohesion, and performance, meaning that group cohesion, and performance increase as diversity decreases (Harrison, Price, & Bell, 1998;Simons, Pelled, & Smith, 1999;Wiersema & Bantel, 1992). And, finally, Ancona and Caldwell (1992) and Smith et al (1994) report a null relationship-that diversity and group cohesion have no relationship with performance.…”
Section: Diversity Performance and Cohesionmentioning
confidence: 99%
“…This happens because as group members discuss their individual perspectives, conflict may occur where each group member argue over which viewpoint is better. Such conflict is considered to foster the environment for innovative solutions and creativity in general (Ancona & Caldwell, 1992;Bantel & Jackson, 1989;De Dreu et al, 2001) …”
Section: Social Category and Functional Diversity Perspectivementioning
confidence: 99%
“…Ancona & Caldwell, 1992;Lovelace et al, 2001;Reagans et al, 2001). Many Research studies have indicated that since service-oriented industries are involved more frequent and closer interactions with customers, enhancing diversity based on demographic attributes in such industries can actually enhance a firm's "market competence" giving it a competitive advantage in the service industry (Richard et al, 2007).…”
Section: Industry Setting and Team Diversitymentioning
confidence: 99%